The effect of high-intensity intermittent functional training towards the aerobic fitness of youth badminton players - Joummy, A. J.; Suppiah, P. K.; Samsir, S. (Malaysian Journal of Movement, Health and Exercise, 2020)
The main objective of this study is to measure the effectiveness of high-intensity intermittent functional training on aerobic fitness of youth badminton players. A total of 16 male participants of the 13 to 15 years old badminton players underwent a ten (10) weeks of intervention training. All participants must undergo a 20m Multistage Fitness test to measure their maximum oxygen intake ("V" O2max). The participants were randomly divided into two groups, Experiment (n = 8) and Control (n = 8) based on the results of aerobic fitness assessment. The Experimental Group will perform a high-intensity intermittent functional training whilst the Control Group performs the traditional training which is the regular exercise routine in their training program. After the 10-week interval training, there was a significant difference observed in the maximum oxygen intake ("V" O2max) between the Experimental and Control groups, F (1,14) = 4.663, p = .049. In conclusion, high-intensity intermittent functional training can improve aerobic fitness amongst youth badminton players.